2011
DOI: 10.1590/s1517-83822011000100010
|View full text |Cite
|
Sign up to set email alerts
|

Xylanase and cellulase activities during anaerobic decomposition of three aquatic acrophytes

Abstract: Enzymatic activity during decomposition is extremely important to hydrolyze molecules that are assimilated by microorganisms. During aquatic macrophytes decomposition, enzymes act mainly in the breakdown of lignocellulolytic matrix fibers (i.e. cellulose, hemicellulose and lignin) that encompass the refractory fraction from organic matter. Considering the importance of enzymatic activities role in decomposition processes, this study aimed to describe the temporal changes of xylanase and cellulose activities du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…These results may be explained by the degradation of xylan networks between cellulose microfibrils, which allows endoglucanase to degrade cellulose microfibrils in the deeper structure (14). Similar synergistic effect was reported for other xylan and cellulose degrading enzymes (14, 15). …”
Section: Resultssupporting
confidence: 86%
“…These results may be explained by the degradation of xylan networks between cellulose microfibrils, which allows endoglucanase to degrade cellulose microfibrils in the deeper structure (14). Similar synergistic effect was reported for other xylan and cellulose degrading enzymes (14, 15). …”
Section: Resultssupporting
confidence: 86%
“…The values of POC LS for the two species are close to values found for the submerged species (34.1%) (Nunes et al, 2011). The coefficients of mass loss for both species were higher during the first stage of decomposition (first week).…”
Section: Discussionsupporting
confidence: 78%
“…This pattern was due to a more rapid mass loss because of the leaching processes of protoplasmic fractions and subsequent dominance of the decomposition processes of the most recalcitrant fraction (Godshalk and Wetzel, 1978;Danell and Sjoberg, 1979;Ayyappan et al, 1986;Asaeda et al, 2000;Chimney and Pietro, 2006). The t ½ for the decay of organic matter from both species (88 days for E. densa and 94 days for H. verticillata) were low when compared with the values obtained for submerged species in various studies (Cunha and Bianchini Junior, 1998;Bianchini Junior, 1999, 2003Asaeda et al, 2000;Nunes et al, 2011): an average of 156 days. However, these periods of half-life can not be accepted as the patterns of the two species because temperature acts as a fundamental role in determining the decay rate of organic matter (Barillier and Garnier, 1993).…”
Section: Discussionmentioning
confidence: 66%
“…These released nutrients can increase the bacterial production (33), causing the enzymatic production peak. Nunes et al (25) also observed an initial peak in cellulase and xylanase production in an in vitro anaerobic experiment with 3 other macrophytes of Óleo lagoon ( Ricciocarpus natans (L.) Corda, Oxycaryum cubense (Poepp. & Kunth) and Cabomba furcata Schult.…”
Section: Discussionmentioning
confidence: 92%